Ethics training for managers : best practice techniques - Watts, Logan L.; Medeiros, Kelsey E.; McIntosh, Tristan J.; Mulhearn, Tyler J. (Oxon: Routledge, 2021)
"Can employees be trained to make more ethical decisions? If so, how? Providing evidence-based and practical answers to these critical questions is the purpose of this book. To answer these questions, the authors-four organizational psychologists who specialize in the study of ethical decision making-translate insights based on decades of scientific research. Whether you are a student, educator, HR manager, compliance professional, or simply someone interested in the topic of ethics education, this book offers a road map for designing ethics training programs that work"--
Includes bibliographical references and index.
Keywords: Personality and managerial performance; Business ethics; Decision making